(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
Spanish-language media in Morocco represent currently an almost unexplored field of research. The present contribution is centred on some aspects of postcolonial (and even, in a large sense, colonial, since we take into account online documents from the Spanish presidios on the Mediterranean coast as well) discours formations in the Spanish-language blogosphere. While discourses focused on postcolonial topics in French blogs have already been analyzed (Torterat, forthcoming), investigations of a similar orientation do not seem to have been carried out on our research object.